ANALISIS TENTANG HADIS-HADIS SATU RAKA’AT SALAT KHAUF - Siregar, Dame (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2014)
Khouf prayer is done when war is happened. If prayer time is coming, war is stopped. The intention is as like the five prayers. This prayer is only rreprensted by one circle of prayer for all based on hadist. It can be done together, but when war is going intensively, it can also be alone done.